Optimizing callus induction and indirect organogenesis in non-dormant corm explants of Gloriosa superba (L.) via media priming - Mosoh, Dexter Achu; Khandel, Ashok Kumar; Verma, Sandeep Kumar; Vendrame, Wagner A. (Frontiers in Horticulture, 2024)
Introduction Gloriosa superba L. is an endangered ornamental plant of significant medicinal, commercial, and cultural value. This study establishes an efficient protocol for rapid in vitro propagation of this plant species through callus-mediated organogenesis using non-dormant corm explants. Methods Plant tissue culture techniques were employed to facilitate the in vitro regeneration process of Gloriosa superba L. This encompassed various stages, including the acquisition of plant material, surface sterilization, formulation of growth media, and the execution of callogenesis, shooting, rooting, and acclimatization experiments. Results and Discussion Investigation into the impact of plant growth regulators on callogenesis unveiled diverse callus morphologies, dependent on regulator type and concentration, with the NAA and KN combination emerging as the most effective for callus induction. Specifically, the callus induction medium supplemented with 1.5 mg L−1 NAA, 0.5 mg L−1 KN, and 10 mg L−1 casein hydrolysate (CH) achieved remarkable results, boasting an 81.25% callus induction rate and a substantial callus biomass fresh weight of 333 mg. Furthermore, the combination of BAP and NAA facilitated optimal shoot primordia induction and shooting in callus derived from non-dormant corm explants. The shoot induction medium, enriched with 2.0 mg L−1 BAP, 0.5 mg L−1 NAA, 5 mg L−1 CH, and 20% (v/v) coconut water (CW), resulted in an impressive 83.33% shoot primordia formation rate and an average of 6.86 shoot primordia per callus. For root induction, the medium supplemented with 1.0 mg L−1 IBA displayed a high root induction rate of 81.25% and robust rooting (+++). Successful acclimatization of in vitro plantlets in controlled environments and shade net houses culminated in thriving growth, and upon transplantation into a garden soil blend (garden soil : sand : vermiculite, 2:1:1, v/v), with direct sunlight exposure, the plantlets demonstrated commendable development and form, boasting a 69% survival rate at the seven-week mark. These findings offer a robust foundation for scalable and sustainable propagation strategies, ensuring the conservation and utilization of this valuable species.